Uji Efek Tonikum Ekstrak Etanol Daun Pecut Kuda (Stachytarpheta jamaicensis L. Vahl) pada Mencit Putih Jantan (Mus musculus): The Tonicum Effect of Ethanolic Extract of Stachytarpheta jamaicensis Leaves in White Mice Male (Mus musculus) - Yuliawati Yuliawati; Rofifah Dhia Savira; Diah Tri Utami (Jurnal Sains dan Kesehatan, 2022)
Tonic is a substance that can increase the bodys defense system. The stimulant effect that is intertwined with the tonic effect is carried out by the central nervous system. Pecut kuda leaf and bases are useful as stimulants and tonics. This research aims to determine the tonicum effect of ethanolic extract pecut kuda leaf in mice. This was an experimental study with completely randomized group design, using male white mice and divided into five namely two control groups (K- given Na CMC 0,5% and K+ given 13 mg caffeine) and three treatment groups (ethanolic axtract of pecut kuda with a dose 50, 100 and 200 mg/kgBW) and each treatment group was repeated 5 times. The methods used were natatory exhaustion test, hanging test and sleep induction test for the parameters observed were the mice'defense on the surface of the water, the duration of the mice endurance on the hanging device and the time the mice fell asleep.The results of the observation data using Duncan's One Way ANNOVA test. The results showed that the pecut kuda leaf extract was effective against the tonic effect test at doses of 50, 100, 200 mg/kgBW. It can be said that pecut kuda leaf extract at a dose of 200 mg/kgBW has almost the same effect as K+ (13mg caffeine).